If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = 3x + 15 Reorder the terms: 10 + 2x = 3x + 15 Reorder the terms: 10 + 2x = 15 + 3x Solving 10 + 2x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10 + 2x + -3x = 15 + 3x + -3x Combine like terms: 2x + -3x = -1x 10 + -1x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 10 + -1x = 15 + 0 10 + -1x = 15 Add '-10' to each side of the equation. 10 + -10 + -1x = 15 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 15 + -10 -1x = 15 + -10 Combine like terms: 15 + -10 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 4(x+3)+1=5(2x-3)-(x+2) | | 5x=-11 | | 8x+5y=28 | | log(3)5x=log(3)160 | | 29=-3+4x | | 13=-6w | | 8(x)/7+9+30 | | 9*u+7=5(u+3) | | 6(w+1)=2*w+34 | | 6x(6+4x)=26+x | | -8*v-2=-6(v-1) | | .125D-3(D-7)=5.125D-3 | | 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 |